Mercury in zooplankton from the Malacca Straits. - Rezai, H.; Md. Yusoff, Fatimah; Yap, Chee Kong (NISCAIR, 2003)
Total mercury concentration in mixed zooplankton was determined from near surface waters in Malacca Straits (05o 59' N, 99o 59' E and 01o 10' N, 103° 29' E). Total mercury concentrations in mixed zooplankton ranged from 1.12 to 4.68 ng dry weight g-1 with a mean of 2.08 ± 0.25 ng dry weight g-1 and showed a decreasing trend from nearshore to offshore areas. Higher mercury concentrations were found in nearshore waters (mean of 2.79 ± 0.49 ng dry weight g-1). Total mercury content was higher in the southern part of the Straits compared to the other parts. The zooplankton in the Malacca Straits environment is not heavily contaminated with mercury.